Análise do conhecimento de gestantes adolescentes sobre métodos contraceptivos - Jane Savoi Silveira (2021)
Teenage pregnancy is recognized as a global public health problem, most of them being unwanted. To understand why the numbers of cases are still high in Brazil becomes fundamental to develop actions to combat this reality. Numerous interventions have been carried out all over the world, but few have been effective and it can be noticed that the lower income a country has, the more difficult it is for these interventions to be implemented. This cross-sectional study analysed 186 pregnant teenagers included in the prenatal program of the Júlia Kubitchek Hospital, through structured interviews conducted during the admission anamnesis. It aimed to evaluate the teenagers knowledge on contraceptive methods, identifying the encountered difficulties, from the information to the use of them. This research presents data related by the pregnant adolescents and shows that the knowledge on contraceptive methods does not motivate their correct and consistent use, and that the psychological immaturity, which is common in this age group, is an unfavorable factor. Having the research been done with adolescents provided conditions to evaluate the real reasons which led them to abandon the use of contraceptives as well as the level of knowledge they really have about them.